Influenza during pregnancy: Incidence, vaccination coverage and attitudes toward vaccination in the French web-based cohort G-GrippeNet. Issue 20 (29th April 2016) - Loubet, Paul; Guerrisi, Caroline; Turbelin, Clément; Blondel, Béatrice; Launay, Odile; Bardou, Marc; Goffinet, François; Colizza, Vittoria; Hanslik, Thomas; Kernéis, Solen
Abstract: Introduction: Pregnancy is a risk factor for severe influenza. However, data on influenza incidence during pregnancy are scarce. Likewise, no data are available on influenza vaccine coverage in France since national recommendation in 2012. We aimed to assess these points using a novel nationwide web-based surveillance system, G-GrippeNet. Methods: During the 2014/2015 influenza season, pregnant women living in metropolitan France were enrolled through a web platform (https://www.grippenet.fr/ ). Throughout the season, participants were asked to report, on a weekly basis, if they had experienced symptoms of influenza-like-illness (ILI). ILI episodes reported were used to calculate incidence density rates based on period of participation from each participant. Vaccination coverage was estimated after weighing on age and education level from national data on pregnant women. Factors associated with higher vaccination coverage were obtained through a logistic regression with Odds Ratio (OR) corrected with the Zhang and Yu method. Results: A total of 153 women were enrolled. ILI incidence density rate was 1.8 per 100 person-week (95%CI, 1.5–2.1). This rate was higher in women older than 40 years (RR = 3.0, 95%CI [1.1–8.3], p  = 0.03) and during first/second trimesters compared to third trimester (RR = 4.0, 95%CI [1.4–12.0], p  = 0.01). Crude vaccination coverage was 39% (95%CI, 31–47) and weighted vaccination coverage was estimated at 26% (95%CI, 20–34). Health care provider recommendation for vaccination (corrected OR = 7.8; 95%CI [3.0–17.1]) and non-smoking status (cOR = 2.1; 95%CI [1.2–6.9]) were associated with higher vaccine uptake. Conclusion: This original web based longitudinal surveillance study design proved feasible in pregnant women population. First results are of interest and underline that public health policies should emphasize the vaccination promotion through health care providers.